Tumor Patients´ Perceived Changes of Specific Attitudes, Perceptions, and Behaviors Due to the COVID-19 Pandemic and Its Relation to Reduced Wellbeing - Büssing, Arndt; Hübner, Jutta; Walter, Stefanie; Gießler, Wolfgang; Büntzel, Jens (Frontiers in Psychiatry, 2020)
Background During the COVID-19 pandemic, the Working Group “Prevention and Integrative Oncology” (PRIO) in the German Cancer Society has initiated flash interviews and surveys. One of these stated increasing rates of fears and mental stress of tumor patients. Now we aimed to analyze whether tumor patients did perceive changes in their attitudes and behaviors related to their relationships, awareness of nature and quietness, interest in spiritual issues, or feelings of worries and isolation. A further point of interest was how these perceived changes could be predicted, either by meaning in life, spirituality as a resource to cope, perceived fears and worries, or particularly by their wellbeing. Materials and Methods Online survey with standardized questionnaires (i.e., WHO-Five Well-being Index (WHO5), Meaning in Life Questionnaire (MLQ), Spiritual and Religious Attitudes to cope with illness (SpREUK-15), Gratitude/Awe scale (GrAw-7)) among 292 tumor patients (72% men; mean age 66.7 ± 10.8 years; 25% < 60 years, 33% 60-70 years, 41% > 70 years) from Germany between May 6 to June 10, 2020. Results Patients´ wellbeing (WHO5) scores were in the lower range (14.7 ± 6.0); 35% scored < 13, indicating depressive states. Wellbeing was significantly higher in older persons and lower in younger ones (F=11.1, p<.0001). Most were irritated by different statements about the danger and the course of the corona infection in the public media (60%), and 57% were worrying to be infected and to have a complicated course of disease. Because of the restrictions, patients noticed changes in their attitudes and behaviors (measured with the 12-item Perceptions of Change Scale): 1) Perception of nature and silence (Cronbach´s alpha = .82), 2) Worrying reflections and loneliness (Cronbach´s alpha = .80), 3) Interest in spirituality (Cronbach´s alpha = .91), 4) Intense relationships (Cronbach´s alpha = .64). These perceptions of change were similar in women and men, age groups and also with respect to tumor stages. Regression analyses revealed that the factor Perception of nature and silence was predicted best by patients´ ability to value and experience the ‘wonder’ of the present moment (in terms of wondering awe and gratitude) and by patients´ search for meaning in life. The factor Worrying reflections and loneliness was predicted best by their search for meaning in life and by feelings of being under pressure because of the Corona pandemic. Interest in spirituality was predicted best by search for an access to a spiritual source and by frequency of praying. Intense relationships were explained with weak predictive power by patients´ ability to reflect life concerns. Patients´ wellbeing during the Corona pandemic was predicted (R2 =.57) by a mix of disease and pandemic related stressor, and by available resources (meaning in life and religious trust). Conclusion In this study among tumor patients from a secular society the topics meaning in life, having (religious) trust, stable relationships, mindful encounter with nature, and times of reflection were found to be of importance. To overcome tumor patients´ feelings of isolation, depressive states, and insecurity about future perspectives, further support is needed, particularly in their socio-spatial surrounding. These are the domains of psychotherapy and spiritual care. The planned integration of structured access to spiritual care seems to be important, not only for the field of cancer care. As the findings refer to patients´ self-perceptions, longitudinal studies are required to substantiate these perceived changes.